2018
DOI: 10.1016/j.acmx.2017.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Determinación del valor pronóstico a 6 meses del puntaje de riesgo OESIL en una cohorte colombiana con síncope evaluada en el servicio de urgencias, primera experiencia latinoamericana

Abstract: A score above or equal to 2 in the OESIL risk score applied in Colombian population was of limited use to predict the studied severe outcomes. This score will be unable to discriminate between patients that benefit of early admission and further clinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…This way, syncope becomes a challenge for the emergency clinician when defining which patients must be properly admitted and observed. In this context, there is a need for tools capable of predicting the risks of mortality or other serious outcomes, both in the short and long term (DÍAZ-TRIBALDOS DC, et al, 2018) Scales that can be used to assess shortterm outcomes include the São Francisco scale, for predicting death and critical events within 1 week; the Boston Scale, ROSE and the Canadian Syncope Risk Score, which seek to predict serious events within 30 days. The EGSYS and OESIL scales, in turn, are used for long-term assessment, the first to predict serious outcomes in one year and the second in two years (DÍAZ-TRIBALDOS DC, et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…This way, syncope becomes a challenge for the emergency clinician when defining which patients must be properly admitted and observed. In this context, there is a need for tools capable of predicting the risks of mortality or other serious outcomes, both in the short and long term (DÍAZ-TRIBALDOS DC, et al, 2018) Scales that can be used to assess shortterm outcomes include the São Francisco scale, for predicting death and critical events within 1 week; the Boston Scale, ROSE and the Canadian Syncope Risk Score, which seek to predict serious events within 30 days. The EGSYS and OESIL scales, in turn, are used for long-term assessment, the first to predict serious outcomes in one year and the second in two years (DÍAZ-TRIBALDOS DC, et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The study calculated a sensitivity of 96.8% and a specificity of 72.8%, which may allow more accurate stratification and targeting of diagnostic procedures and therapeutic interventions. Similarly, other studies [ 15 , 18 , 20 , 32 - 34 ] have validated the OESIL risk score using different study designs, different endpoints, and different individuals who interpreted the ECG. The results suggested that the prediction accuracy of OESIL in other syncope populations is significantly reduced, so it has not been promoted in clinical applications.…”
Section: Prognostic Scores For Long-term Outcomesmentioning
confidence: 95%